PENERAPAN SISTEM POINT OF SALE GUNA MEMBANTU PEMILIK TENANT MENGELOLA USAHA DI SOCIALSIP ULUWATU - I Komang Dwiprayoga; Made Agung Raharja; I Wayan Santiyasa (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The operation of sales and warehouse management at SOCIALSIP Uluwatu presents challenges for tenants in managing transactions and business operations efficiently. In this context, a web-based Point of Sale (POS) system becomes the primary solution to integrate transactions, simplify data processing, and enhance efficiency and security. This study aims to develop a POS system that meets the tenants' needs through various features, such as sales recording, inventory management, payment method integration, and data reporting. By adopting a tenant-centered development approach, this initiative not only provides a technological solution but also empowers tenants through improved digital literacy.